Traditional medicine use in two public South African hospitals: Prevalence and interactive antimicrobial studies for combinations with conventional antimicrobials - Booth, Zelna (University of the Witwatersrand, Johannesburg, 2025)
Traditional medicines are entrenched in the cultural heritage of many South Africans. Integrative medicine involves the harmonised use of traditional medicine and conventional healthcare. The diverse availability of traditional medicinal plants and accessibility to many commercial muthi markets in South Africa lends itself to a noteworthy, alternate source of healthcare. A three-phase study was thus designed to explore integrative medicine in South Africa. Phase 1 of this study aimed to document existing literature on antimicrobial synergism or antagonism between natural products and conventional antimicrobials in a systematic framework to provide a valuable resource highlighting antimicrobial synergism or to draw attention to harmful interactions to be avoided in clinical practice (antagonism). Phase 2 of this study aimed at investigating the prevalence of use of traditional medicine, amongst patients at two large public hospitals in South Africa, namely Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) in Johannesburg (JHB) and King Edward Hospital VIII (KEH) in KwaZulu-Natal (KZN) and further discern the extent of concurrent use with conventional medicines. Phase 3 aimed to determine the in vitro interactive antimicrobial and toxicity profiles of conventional antimicrobials in combination with traditional, medicinal plants most prevalently used for infectious diseases, purchased from two major muthi markets in South Africa (Faraday market in JHB and Warwick market in KZN). Phase 1 of the study involved a systematic review of the literature, according to PRISMA methodology, with the inclusion of all interactions of synergy and antagonism documented within the past 20 years. In phase 2 of the study, a descriptive, self-administered, quantitative survey, consisting of demographic; and traditional medicine use was undertaken. Data analysis included quantitative frequencies and percentages. Ethical clearance (M190534) was obtained for the study. For phase 3, plant material was collected from the muthi markets, botanically identified and thereafter minimum inhibitory concentration (MIC) assays were conducted. Antimicrobial interactions were assessed by calculating the fractional inhibitory concentration (ΣFIC). Interactive toxicity profiles of the synergistic combinations were evaluated using the brine shrimp lethality assay (BSLA).
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, in the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2025
Keywords: Traditional medicine; medicinal plants; antimicrobials; combinations; interactions; toxicity; UCTD; SDG-3: Good health and well-being